A Case of Advanced Gastric Cancer with Folfiri as a Preoperative Chemotherapy - Hieu Van Nguyen; Hung Van Nguyen; Long Thanh Nguyen; Nga Quynh Pham; Hau Xuan Nguyen; Hien Xuan Nguyen; Vuong Thi Nguyen (Case Reports in Oncological Medicine)
Introduction. In advanced gastric cancer, preoperative chemotherapy is associated with survival benefit. FOLFIRI has demonstrated promising results in terms of survival and tolerance, especially in patients with poor performance status. Case Presentation. A 59-year-old male, diagnosed with pT4bN2M0 gastric cancer, underwent gastrointestinal anastomosis and three cycles of EOX chemotherapy. Due to disease progression, he was switched to FOLFIRI regimen. After 12 cycles, the patient received a subtotal gastrectomy and D2 lymphadenectomy. Microscopic examination achieved pCR, and the patient has been surviving 34 months without recurrence. No severe toxicities of chemotherapy were recorded. Conclusions. FOLFIRI might be a safe and effective option in neoadjuvant treatment for advanced gastric cancer among patients with poor performance status or progression after first-line chemotherapy.